Future Directions in Canadian Industrial Relations - Verma, Anil (Relations industrielles / Industrial Relations, 1992)
The process of research or scientific enquiry is often serendipitous and, like art, inherently creative. The intricacies and complexities of the human mind determine its course. Exigencies such as war and social upheaval often drive its priorities. It is difficult, therefore, if not impossible, to chart out research directions the way corporations plot market strategies. Nevertheless, it is useful (even necessary, some would argue) to make some assessments of the directions in Industrial Relations (IR) research, past and present, and to speculate on its potential. It is with these ideas in mind that the Canadian Industrial Relations Association (CIRA) invited a panel of researchers and practitioners to address the issue of future directions at the meetings in Victoria in June 1990. This paper and those that follow grew out of the discussions at the panel.